Changes in the form of houses in the earthquake area Cihikeu village, Sarampad, Cigenang, Cianjur - Widajanti, Andjar; Ramadhan, Juang Esa; Hasan, Raziq (Universitas Mercu Buana, 2025)
Cihikeu Village, Sarampad Village, Cianjur Regency, is an earthquake area. From the initial survey of several residential houses in Cihikeu Village, several of the residential houses that experienced minor damage were buildings with stilt structures and woven bamboo/wood walls. Meanwhile, the houses that suffered heavy damage due to the earthquake were walled buildings. The change in the form of residential buildings in Cihikeu Village, Cianjur, which were originally structures on stilts to become permanent buildings with walls, raises the question: What factors were behind them making this change? This research uses qualitative methods, namely observation and interviews to determine changes in building shape and what factors influence these changes in shape. The results of the research resulted in changes in the shape of the building in Cihikeu Village, it experienced heavy damage caused by several things, namely: economic factors, maintenance factors and insight factors from the external environment. The impact of the earthquake where residents received assistance from certain foundations caused residents to add bathrooms, where currently residents use public bathrooms.